Automation and Universal Basic Income: Employment Options under Technological Shock - Bai, Chuhan (International Journal of Computer Science and Information Technology, 2025)
Automation is impacting the world of work, with many low-skilled jobs being lost to technology in areas such as manufacturing, services and healthcare. However, new roles have also been created, such as robot maintenance and programming, as well as data analysts and AI trainers. The job market is experiencing a coexistence of both "difficult to find" and "difficult to recruit" jobs. To cope with this, the concept of universal basic income (UBI) has been proposed. UBI is based on the theory that it provides economic security for all members of society and encourages choice. It is not linked to work incentives, means tests, etc., and recipients can spend the money as they wish. Alaska’s dividend system has been linked to improvements in financial and psychological well-being, as well as employment and poverty reduction. Finland’s basic income experiment aimed to boost employment, but its effect has been modest. While UBI is valuable, it should be combined with other employment policies, such as retraining and career transition support, to achieve social stability and sustainable economic development.